'n Vergelyking van die persepsies van die relatiewe belang van evalueringskriteria tussen verbruikers en verkoopskonsultante by die aankoop van 'n passasiersmotorvoertuig - P. J. Du Plessis; C. Boshoff (South African Journal of Business Management, 1988)
– The acceptance of the marketing concept and the implementation of the principles on which it is based presupposes a thorough knowledge of market needs. If the marketing concept is applied at retail level in the South African motor industry, one should be able to assume that there is a high degree of agreement regarding the perceptions of consumers and sales personnel of what is important to a purchaser when buying a motor vehicle. The validity of this statement was tested by means of the following null-hypothesis: There is no difference with regard to the relative importance attached to different evaluation criteria between consumers and sales personnel, with the purchase of a passenger vehicle. Information provided by 902 consumers and 200 sales personnel revealed that significant differences (p 0,01) exist between the two groups with regard to 35 evaluation criteria and a further four criteria on the 0,05 level. The null-hypothesis is thus rejected with regard to 39 evaluation criteria in favour of the alternate hypothesis.
Keywords: 650